Post-error slowing in sequential action: an aging study - Ruitenberg, Marit; Abrahamse, Elger; De Kleine, Elian; Verwey, Willem B. (Frontiers in Psychology, 2014)
Previous studies demonstrated significant differences in the learning and performance of discrete movement sequences across the lifespan: Young adults (18-28 years) showed more indications for the development of (implicit) motor chunks and explicit sequence knowledge than middle-aged (55-62 years; Verwey et al., 2011) and elderly participants (75-88 years; Verwey, 2010). Still, even in the absence of indications for motor chunks, the middle-aged and elderly participants showed some performance improvement too. This was attributed to a sequence learning mechanism in which individual reactions are primed by implicit sequential knowledge. The present work further examined sequential movement skill across these age groups. We explored the consequences of making an error on the execution of a subsequent sequence, and investigated whether this is modulated by aging. To that end, we re-analyzed the data from our previous studies. Results demonstrate that sequencing performance is slowed after an error has been made in the previous sequence. Importantly, for young adults and middle-aged participants the observed slowing was also accompanied by increased accuracy after an error. We suggest that slowing in these age groups involves both functional and non-functional components, while slowing in elderly participants is non-functional. Moreover, using action sequences (instead of single key-presses) may allow to better track the effects on performance of making an error.